Correlation Between Internal Carotid Artery Tortuosity and Imaging of Cerebral Small Vessel Disease - Chen, Yuan-Chang; Wei, Xiao-Er; Lu, Jing; Qiao, Rui-Hua; Shen, Xue-Feng; Li, Yue-Hua (Frontiers in Neurology, 2020)
Background and purpose: An association between artery tortuosity and neuroimaging of cerebral small vessel disease (SVD) has been reported, especially in the posterior circulation. However, few studies involved the whole magnetic resonance imaging (MRI) spectrum of SVD in association with anterior circulation arterial tortuosity. This study aimed to investigate the relationship between internal carotid artery (ICA) tortuosity and the neuroimaging of SVD. Methods: Data of 1264 consecutive patients in whom cerebral vessel diseases were suspected and who underwent both MRI and computed tomography angiography (CTA) were reviewed from a prospective registry. ICA tortuosity was evaluated using the tortuosity index (TI), which was defined as the ratio of the vessel centerline length divided by the straight length. MRI was used to assess cerebral microbleeds (CMBs), white matter hyperintensities (WMHs), enlarged perivascular spaces (EPVSs), and lacunes. Results: The TIs of the ICA for patients with SVD and patients without SVD were 1.81 ± 0.42 and 1.72 ± 0.33, respectively (P < 0.001). Univariate analysis showed that the ICA TI were positively correlated with each SVD MRI marker (P < 0.001), and the correlation coefficients (rs) were 0.57, 0.42, 0.30, and 0.26 for EPVSs, WMHs, CMBs, and lacunes, respectively. The adjusted ORs of the ICA TI were 1.52 (95% CI 1.44-1.60, P < 0.001) for EPVS grade 1, 2.05 (95% CI 1.93-2.18, P < 0.001) for EPVS grades 2-4, and 1.09 (95% CI 1.03-1.15, P = 0.004) for WMH grade 3. Conclusions: The TI of ICA was higher in patients with SVD. ICA tortuosity was associated with MRI-defined markers of SVD, including EPVS and high-grade WMH, and positively correlated with EPVS severity. Arterial tortuosity might be a risk factor for SVD. This finding may have potential clinical significance for identifying patients with SVD.